Effect of various silica-supported nickel catalyst on the production of bio-hydrocarbons from oleic acid - Riyandi, Rafly; Rinaldi, Nino; Yunarti, Rika Tri; Dwiatmoko, Adid Adep; Simanjuntak, Fidelis Stefanus Hubertson (International Journal of Renewable Energy Development, 2024)
The conversion of fatty acids into bio-hydrocarbons can be carried out through a deoxygenation (DO) reaction. Catalytic deoxygenation of fatty acids can occur through three reaction pathways: decarbonylation, decarboxylation, and hydrodeoxygenation. In this study, three kinds of silica were prepared: (i) silica obtained from the rice husk ash (RHA); (ii) synthetic mesoporous silica SBA-16; and (iii) commercial silica. All prepared silica was used as supported nickel (Ni) catalyst for bio-hydrocarbon production through DO reaction of oleic acid. The objective of this study was to investigate the effect of variations of silica on the reaction pathway and final products composition of DO reaction of oleic acid. The catalysts were characterized by X-ray fluorescence (XRF), X-ray diffraction (XRD), surface area analysis, and NH3-temperature-programme desorption. Based on XRF and XRD analysis results, it can be concluded that nickel was successfully impregnated into all silica. All samples of catalysts were used in a reaction carried out at temperature of 285 °C under a pressure of 40 bar H2 for 2h. The results showed that all catalysts were able to convert oleic acid to bio-hydrocarbon with differences in products composition. The highest oleic acid conversion of 98.25% was achieved with Ni/RHA catalyst but the obtained liquid products was the lowest among other catalysts. It is found that this phenomenon was closely related to the acidity properties of the catalyst.